2012
DOI: 10.1093/chromsci/bms155
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Rutin in the Extract and Gel of Viola tricolor

Abstract: Heartsease, also known as wild pansy (Viola tricolor L.), contains considerable amounts of polyphenols: 109.32 ± 1.29 mg of Gallic acid equivalent/g of extract. This study investigates their phytoconstituents and antioxidant capacity and validates a method for the quantification of rutin in the crude extract of the flowers of V. tricolor and in the extract incorporated in gel. Much better antioxidant capacity was found for the extract [inhibition concentration (IC50) of 16.00 ± 0.78 µg/mL] than the standard as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…The rutin content for the saline extract and fraction was 0.53 ± 0.0010% and 0.24 ± 0.0033%, respectively. Our results are similar to studies with BmoLL conjugated with quantum dots [ 20 ] which showed an HA of 1024 in hemagglutination tests, as well as in studies with extract of Viola tricolor [ 27 ] and ethanol extract of Caesalpinia pyramidalis [ 28 ] regarding the presence of this metabolites.…”
Section: Resultssupporting
confidence: 90%
“…The rutin content for the saline extract and fraction was 0.53 ± 0.0010% and 0.24 ± 0.0033%, respectively. Our results are similar to studies with BmoLL conjugated with quantum dots [ 20 ] which showed an HA of 1024 in hemagglutination tests, as well as in studies with extract of Viola tricolor [ 27 ] and ethanol extract of Caesalpinia pyramidalis [ 28 ] regarding the presence of this metabolites.…”
Section: Resultssupporting
confidence: 90%
“…41 HPLC is a versatile, robust, and widely used technique used in phytochemical and analytical chemistry for quantification, identification and purification of the mixture components. 42 Moreover this technique is also useful for characterization and quantification of secondary metabolites in plant extract. 43 HPLC studies revealed that concentration of lupeol in Pyrus pashia ethanolic exract was 4.24% w/w.…”
Section: Discussionmentioning
confidence: 99%
“…It is used in analytical chemistry and phytochemistry to separate a mixture of substances. HPLC is a robust, dependable, and widely used method for the isolation of natural substances [40][41]. For measuring and characterizing secondary metabolites in plant extracts, such as phenol compounds, flavonoids, alkaloids, steroids, and other steroid-like substances, HPLC has been advocated in various articles [42][43][44][45][46].…”
Section: Hplcmentioning
confidence: 99%